2019
DOI: 10.1155/2019/9236742
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Decline after 24 Weeks of Moxa Smoke Exposure in Rats

Abstract: Objective Moxibustion is a complementary therapy that has been used for thousands of years. Burning moxa produces smoke and inhalable particulates. Recent research has indicated that smoke inhalation is associated with negative lung effects. This study aimed to evaluate the lung function of rats after moxa smoke exposure at different concentrations. Methods Using a randomised block experiment design, 28 male Wistar rats were randomly divided into three moxa smoke groups (opacity) (n=7): low concentration (27.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…However, all results surprisingly demonstrated clinical efficacy and safety of MS under the carefully designed concentration, totally out of expectations. [58][59][60][61][62][63] Therefore, our hypothesis is that the efficacy and safety of MS possibly should be affected by the level of MSC, moxa quality and duration of exposure in MS. Firstly, moxa aged more than three years is considered as quality guarantee for its characteristics, and the moxibustion duration usually lasts for 20-30 min for each session. 64 Hence, moxa that has been aged for three years will be utilized in 30-minute treatment sessions in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…However, all results surprisingly demonstrated clinical efficacy and safety of MS under the carefully designed concentration, totally out of expectations. [58][59][60][61][62][63] Therefore, our hypothesis is that the efficacy and safety of MS possibly should be affected by the level of MSC, moxa quality and duration of exposure in MS. Firstly, moxa aged more than three years is considered as quality guarantee for its characteristics, and the moxibustion duration usually lasts for 20-30 min for each session. 64 Hence, moxa that has been aged for three years will be utilized in 30-minute treatment sessions in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Moxa smoke at higher concentrations might destroy heart, liver, and kidney function. In fact, it has been reported that moxa smoke can cause related symptoms, such as eustachian tube and throat itching, eye pain, tonsil enlargement, and other symptoms [ 30 – 33 ]. Tar contains two-tenths of a million of a kind of thick cyclic aromatic hydrocarbon called benzo(a)pyrene, which is a strong carcinogen [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, animal research conducted by He et al also demonstrated that the FEV1/FVC%, inspiratory resistance, and expiratory resistance among each group after 24 weeks of MSE had no difference. It was also mentioned that MSE at low concentrations did not affect the rat's lung function and moxa smoke of low concentrations (27.45 mg/m 3 ) is much higher than that in a regular moxibustion clinic (3.54 mg/m 3 ) [34]. Furthermore, animal research carried out in another study indicated that long-term MSE with medium and high concentration may cause inflammatory changes in the lung and bronchi, but it was not obvious in low concentration.…”
Section: Discussionmentioning
confidence: 99%